Pentingnya ekonomi kreatif sebagai probabilitas atensi mahasiswa gen Z: Meningkatkan kompetensi dalam menciptakan inovasi baru - Adzkiya, Hida Amalia (Maliki Interdisciplinary Journal, 2023)
Creative Economy is a concept to realize more advanced and sustainable economic development based on creativity and innovative aspects (yunaz et al., 2022). The background to writing this scientific paper is that Gen Z students, where they are closer to digitalization than previous generations, have not taken advantage of this progress. In fact, they can take advantage of the great opportunities in themselves to be able to advance the Indonesian economy in a way that is more effective and easy to implement, namely through Creative Economy (Creative Economy). The method used in writing this scientific work is Theoretical Development by developing and expanding existing theories through conceptual thinking. There are several sub-sectors of the creative economy, including: product design, fashion, culinary, photography, DKV, crafts, publishing, and applications (Anwar, 2022). This needs to be known by students so that later they can understand what needs to be done to start their role as generation Z in studying creative economics, and it is also hoped that it can advance the Indonesian economy which will create new jobs needed by the community and can increase foreign exchange.